Supply Chain Risk Management for Native Chicken in Taliwang Chicken Culinary Businesses in Mataram City: An Integrated FMEA–AHP Approach - Muh. Prasetyo Nugroho; I Gusti Agung Ayu Ambarawati; Budi Rahayu Tanama Putri; Djoko kisworo; Bulkaini Bulkaini; Novizar Nazir (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2026)
Taliwang chicken is a traditional culinary icon of Lombok, Indonesia, and its supply chain, involving farmers, collectors, and restaurants, faces significant operational vulnerabilities. This study maps the native chicken supply chain using SCOR, identifies failure modes using FMEA, and determines risk priorities using AHP based on survey data from 58 respondents. The supply chain operates linearly from producers to restaurants. Integrating FMEA and AHP identifies price and market risks as the most dominant category (weight: 0.42), with live chicken price fluctuations ranking as the top-priority risk (weighted RPN: 161.28), followed by limited DOC supply, disease mortality, intermediary reliance, and low institutional support. Conclusion: Supply chain stability depends heavily on mitigating price volatility and securing stable inputs. Contribution to Sustainable Development Goals (SDGs): SDG 2: Zero HungerSDG 8: Decent Work and Economic GrowthSDG 9 : Industry, Innovation and InfrastructureSDG 11 : Sustainable Cities and CommunitiesSDG 12: Responsible Consumption and Production